Ground water monitoring strategies to support community management of on-site home sewage disposal systems - Nelson, James D., author; Ward, Robert C., advisor; McWhorter, D. B., committee member; Mielke, P. W., committee member; Hiller, R. L., committee member (Colorado State University. Libraries, 1980)
Organizations which provide centralized management of on-site sewage disposal systems are currently evolving in many areas of the United States. At present, there is no routine feedback for management agencies regarding their efforts in preventing ground water contamination. Ground water monitoring is necessary to provide these agencies with the information they need to maintain ground water quality. This research is directed toward supplying monitoring strategies for that purpose. Ground water monitoring strategies presented herein were developed by combining deterministic and probabilistic approaches. The variables which need to be considered in such a monitoring program are discussed. Two types of monitoring are defined which need to be incorporated into an overall management plan. Inspection monitoring refers to the monitoring of individual systems to determine if they are exceeding their design discharge of pollutants to the ground water. Trend monitoring is defined as the monitoring which detects over time and space the cumulative effect of a management agencies pollution control efforts. Inspection monitoring strategies are developed in terms of the sampling frequencies necessary to obtain a specific probability of detecting system failure. A mathematical model describing the flow of pollutants through the leach field is developed for the purpose of evaluating sampling plans and a sensitivity analysis is performed to determine the effect of varying the parameters of the system and the input to the leach field. The discussion of trend monitoring strategies is based primarily on existing statistical theory. Sampling frequency is discussed in terms of the number of samples required to obtain an estimate of the mean of a water quality variable within specified confidence limits. The effect of spatial and serial correlation is also considered. Finally, a discussion of various sampling techniques applicable to ground water monitoring is presented.
Keywords: Sewage disposal plants; Groundwater -- Pollution